QRIS: Solusi Pembayaran Digital di Bank Syariah Indonesia untuk UMKM - Ema Elisa; Nia Zulinda (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the role of the Quick Response Code Indonesian Standard (QRIS) as a digital payment solution at Bank Syariah Indonesia (BSI) in enhancing convenience, security, efficiency, and customer satisfaction in transactions for Micro, Small, and Medium Enterprises (MSMEs) in Pontianak, West Kalimantan. A qualitative approach with a descriptive design was employed, utilizing data collected through in-depth interviews, participatory observations, and open-ended questionnaires distributed to MSME customers actively using QRIS at BSI. The findings revealed that QRIS significantly simplifies transaction processes for MSME entrepreneurs, reduces queuing time, and minimizes the risk of transaction errors. Additionally, QRIS enhanced customer data protection through data encryption and dual authentication, aligning with Sharia principles that emphasize security and fairness. Furthermore, the adoption of QRIS has proven to lower the high operational costs associated with conventional transactions, thereby improving business efficiency and MSME productivity. The ease of use, transaction security, and efficiency provided by QRIS not only enhanced user convenience but also strengthen customer trust in Islamic banking services. Overall, this study confirms that QRIS is effective in supporting the growth and sustainability of MSMEs in Indonesia while promoting broader Islamic financial inclusion by upholding values of transparency and fairness